Post-Harvest Handling and Value Addition ICRISAT Kiboko Research Station - Ojulong, Henry; Wafula, Kelvin (International Livestock Research Institute, 2025)
International Crops Research for the Semi-Arid Tropics (ICRISAT) through financial support from Accelerating the Impacts of CGIAR Climate Research for Africa (AICCRA) project has the mission to work towards sustainable local community empowerment, food security and prosperity by promoting drought tolerant crops (DTCs). The project has been working with smallholder farmers in the lower eastern counties of Makueni, Kitui and Taita Taveta. Historically, these three counties have experienced recurrent droughts characterized by consecutive seasons of depressed and poorly distributed rainfall, referred to as arid and semi-arid lands (ASALs). This coupled with poor soil fertility, poor crop husbandry practices and use of poor-quality seeds have led to declining crop production. Majority of farmers over time have stuck to planting the usual crops such as maize, common beans which are highly susceptible to climate change as their water demand per season is high.